The The Health and Adolescents’ Potential Community Movement - Ema Waliyanti; Faudyan Eka Satria; Dewi Puspita (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
Community nurses have an important role in the current society. A number of roles are inherent in community nurses, among them, prevention, maintenance, health promotion and recovery of community diseases. The teenagers become one of the target of community nurses, in case of health care development. Among of them, the Narcotics, Psychotropics, and Addictive Substances (NAPZA) abuse and sex are things that need to be followed up. This can be agreed upon the case studies on Kalipucang Village, Tamantirto, Kasihan, Bantul, which show that some adolescents are involved in deviant behavior, such as drinking alcohol, drug abuse, and unexpected pregnancy –as the result of a lack of understanding of these two things. For this reason, the Youth Health Care and Potential Community Movement (GEMA PESTA REMAJA) activity be held. These activities include health screening, health education, formation and training of Youth Healthcare Services or Posyandu Remaja cadres, as well as optimizing the role of these cadres in managing the Posyandu Remaja that formed. The results of this activity showed a significant changes for the teenagers of Kalipucang Village. This can be seen from the increase in the knowledge of adolescents, which is measured through a post-test, about drug and reproductive health that they get from a series of GEMA PESTA REMAJA activities.